PENGGUNAAN PARALELISME SEJARAH ISRAEL DI PADANG GURUN OLEH PAULUS DALAM 1 KORINTUS 10:1-33 - Arman Susilo (Jurnal Pistis: Teologi dan Praktika, 2021)
This study aims to find Paul's biblical solutions to the problems of the Corinthians in 1 Corinthians 10:1-33. The Corinthians has faced the domination of Greco-Roman religions, that affected their Christians faith. This study tries to approach the text by using a general interpretation approach, followed by an epistolary interpretation approach. A narrative parallelism approach as a literary device is used to conclude the meaning of 1 Corinthians 10:1-33. Paul's use of parallelism in 1 Corinthians 10:1-33 renders principles of the Christian faith in several points. First, fellowship with God will not be managed only through participation in the Baptism sacrament and Eucharist sacramen without a commitment to live holy before Him. Second, Christian freedom is not based on legal knowledge, but on how that legal knowledge can help to grow other people's faith and results to their salvation. Third, there is a need for discipline for believers in sustaining a commitment to communion with God. For communion can never take place without a commitment to God.